Starches-from current models to genetic engineering - Sonnewald, Uwe; Kossmann, Jens (Plant Biotechnology Journal, 2013)
As the world's second most abundant biopolymer, starch serves as food, feed and renewable resource for bioenergy production and other industrial applications. Unlike storage lipids, starch is stored in the form of semi-crystalline granules, which are tissue- and species-specific in number, shape and size. Over the last decades, most biosynthetic and degradative enzymes of starch metabolism have been identified in the model species Arabidopsis thaliana. Based on this, biotechnological applications have arisen that led to a number of transgenic crop plants with elevated starch content or improved starch quality. Irrespective of this great success, there are still numerous open questions including the regulation of starch metabolism, the initiation of granule formation, the regulation of granule shape and size and many more, which will be tackled over the next decades. Here, we briefly summarize current knowledge concerning starch metabolism and its regulation and biotechnological use.
Keywords: starch synthesis; starch degradation; regulation of starch metabolism